2010
DOI: 10.1007/s11666-010-9566-0
|View full text |Cite
|
Sign up to set email alerts
|

Design of Experiment Analysis of the Sulzer Metco DJ High Velocity Oxy-Fuel Coating of Hydroxyapatite for Orthopedic Applications

Abstract: High Velocity Oxy-Fuel (HVOF) has the potential to produce hydroxyapatite (HA; Bio-ceramic) coatings based on its experience with other sprayed ceramic materials. This technique should offer mechanical and biological results comparable to other thermal spraying processes, such as atmospheric plasma thermal spray, currently FDA approved for HA deposition. Deposition of HA via HVOF is a new venture especially using the Sulzer Metco Diamond Jet (DJ) process, and the aim of this article was to establish this techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 16 To conclude this section, plasma spayed [202][203][204][205][206][207][208][209]. Sometimes, this deposition process is also called thermal printing [210].…”
Section: Plasma Sprayingmentioning
confidence: 99%
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 16 To conclude this section, plasma spayed [202][203][204][205][206][207][208][209]. Sometimes, this deposition process is also called thermal printing [210].…”
Section: Plasma Sprayingmentioning
confidence: 99%
“…The powder partially melts in the stream and deposits upon the substrate. The resulting calcium orthophosphate coatings, layers and films have a low porosity and a high adhesion strength (Oguchi et al 1992; Sobolev and Guilemany 1996; Haman et al 1999; Li et al 2000, 2002a; Khor et al 2003a, 2003b, 2004; Hasan and Stokes 2011). …”
Section: Reviewmentioning
confidence: 99%
“…34 Numerous studies have reported the production of HA coatings by thermal spray processes. [35][36][37][38][39][40] However, few have attempted to produce HA by the induction suspension plasma spray process. 41,42 HA production by induction suspension plasma spraying was first achieved by Bouyer et al 41 at the Universite de Sherbrooke Plasma Center.…”
Section: Bibliography Review Ha and Plasmamentioning
confidence: 99%